Features Of Uzbek Music Art - Umurzakov Islam Ilkhom ugli (Zien Journals, 2025)
Uzbek musical art is a complex creative system that embodies the centuries-old historical, spiritual, and cultural experience of our people, harmonizing traditional and modern aspects. In the process of its formation, the influence of various civilizations, including elements of Iranian, Turanian, Indian, and Islamic cultures, was noticeable. At the same time, these influences, subordinate to local national identity, created unique syncretic images and musical structures. Uzbek musical art is distinguished by its ancient roots, genre and stylistic diversity, philosophical and aesthetic content, and deep socio-spiritual foundations. This art form has been formed over the centuries and has developed in close connection with the lifestyle, customs, rituals, and worldview of the people. Uzbek folk music has been passed down from generation to generation on the basis of oral tradition, in which national melodies, tunes, the system of maqoms, the art of composition and performance culture are reflected. The article analyzes the unique stylistic and performance characteristics of Uzbek musical art. The role of maqom and folklore songs in the development of Uzbek musical art has also been studied.
Keywords: music; art; Uzbek; character